Effects of Suvorexant, an Orexin Receptor Antagonist, on Sleep Parameters as Measured by Polysomnography in Healthy Men - Sun, Hong; Kennedy, William P.; Wilbraham, Darren; Lewis, Nicole; Calder, Nicole; Li, Xiaodong; Ma, Junshui; Yee, Ka Lai; Ermlich, Susan; Mangin, Eric; Lines, Christopher; Rosen, Laura; et al. (Sleep (New York, N.Y.), 2013)
Suvorexant (MK-4305) is an orexin receptor antagonist being developed for the treatment of insomnia. This report describes the effects of nighttime administration of suvorexant on polysomnography (PSG) sleep parameters in healthy young men. Randomized, double-blind, placebo-controlled, 4-period crossover PSG study, followed by an additional 5(th) period to assess pharmacokinetics. Sleep laboratory. Healthy young men between 18 and 45 years of age (22 enrolled, 19 completed). Periods 1-4: suvorexant (10 mg, 50 mg, or 100 mg) or placebo 1 h before nighttime PSG recording. Period 5: suvorexant 10 mg, 50 mg, or 100 mg. In Periods 1-4, overnight sleep parameters were recorded by PSG and next-morning residual effects were assessed by psychomotor performance tests and subjective assessments. Statistically significant sleep-promoting effects were observed with all doses of suvorexant compared to placebo. Suvorexant 50 mg and 100 mg significantly decreased latency to persistent sleep and wake after sleep onset time, and increased sleep efficiency. Suvorexant 10 mg significantly decreased wake after sleep onset time. There were no statistically significant effects of suvorexant on EEG frequency bands including delta (slow wave) activity based on power spectral analysis. Suvorexant was well tolerated. There was no evidence of next-day residual effects for suvorexant 10 mg. Suvorexant 50 mg statistically significantly reduced subjective alertness, and suvorexant 100 mg significantly increased reaction time and reduced subjective alertness. There were no statistically significant effects of any suvorexant dose on digit symbol substitution test performance. In Period 5, plasma samples of suvorexant were collected for pharmacokinetic evaluation. The median T(max) was 3 hours and apparent terminal t(½) was 9-13 hours. In healthy young men without sleep disorders, suvorexant promoted sleep with some evidence of residual effects at the highest doses.